2005
DOI: 10.1523/jneurosci.1163-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Excitatory Synaptic Integration by GABAergic Inhibition in the Subthalamic Nucleus

Abstract: The activity patterns of subthalamic nucleus (STN) neurons, which are intimately related to normal movement and abnormal movement in Parkinson's disease (PD), are sculpted by feedback GABAergic inhibition from the reciprocally connected globus pallidus (GP). To understand the principles underlying the integration of GABAergic inputs, we used gramicidin-based patch-clamp recording of STN neurons in rat brain slices. Voltage-dependent Na ϩ (Na v ) channels actively truncated synthetic IPSPs and were required for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
143
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(153 citation statements)
references
References 97 publications
6
143
0
Order By: Relevance
“…It has been shown that blocking glutamatergic neurotransmission has anti-parkinsonian effects in a variety of rodent and primate models of Parkinson's disease (Greenamyre, 1993;Lange et al, 1997), which provides initial support to this prediction in relation with w SG . Further, it has been shown that the inhibition from GPe to STN is crucial for the appearance of beta oscillations in the STN-GPe network (Baufreton et al, 2005).…”
Section: Relationship To Experimental Datamentioning
confidence: 99%
“…It has been shown that blocking glutamatergic neurotransmission has anti-parkinsonian effects in a variety of rodent and primate models of Parkinson's disease (Greenamyre, 1993;Lange et al, 1997), which provides initial support to this prediction in relation with w SG . Further, it has been shown that the inhibition from GPe to STN is crucial for the appearance of beta oscillations in the STN-GPe network (Baufreton et al, 2005).…”
Section: Relationship To Experimental Datamentioning
confidence: 99%
“…With respect to the interplay of excitatory and inhibitory input, GABAergic inhibition can increase the efficiency of STN response to excitatory input by promoting recovery of inactivated voltage-dependent Na+ (Na v ) channels (Baufreton et al, 2005). This process could contribute to the increase in oscillations in the beta frequency (15-30 Hz) range observed in STN after dopamine cell lesion in awake preparations (Baufreton et al, 2005). This appears less suited for shaping slow oscillations, however, as, in the present results, phase relationships show that peak activity in the GP precedes the period of STN bursting by several hundred ms. A recent report by Kass and Mintz (2006), potentially relevant to the firing pattern triggered in the STN by slow antiphase oscillations in cortical and pallidal input, describes three coexisting patterns in STN neurons including pacemaker firing, burst mode, and a bistable state involving a relatively long-lasting silent plateau depolarization that tends to be preceded by a burst discharge.…”
Section: Increased Burstiness and Oscillations In The Stn: Relevance mentioning
confidence: 99%
“…With respect to the interplay of excitatory and inhibitory input, GABAergic inhibition can increase the efficiency of STN response to excitatory input by promoting recovery of inactivated voltage-dependent Na+ (Na v ) channels (Baufreton et al, 2005). This process could contribute to the increase in oscillations in the beta frequency (15-30 Hz) range observed in STN after dopamine cell lesion in awake preparations (Baufreton et al, 2005).…”
Section: Increased Burstiness and Oscillations In The Stn: Relevance mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, both STN and GPe have been shown to fire action potentials coherently with cortical slow oscillations under the influence of cortical input (Magill et al, 2000(Magill et al, , 2001. In this network, the GPe could have a central function in enhancing oscillatory activity in two ways: first, by increasing the capability of the rhythmic excitation from the cortex to drive coherent rhythmic activity in the STN via its recurrent connections with the STN (Baufreton et al, 2005) and second, through increased transmission of cortical activity to the STN via the striatum (Tseng et al, 2001), thus suggesting that a combination of mechanisms involving certain elements of all the above-mentioned hypotheses is at work.…”
Section: Oscillations In Corticobasal Ganglia Circuitsmentioning
confidence: 99%